DEN KULTURELLE PODNING AF DANSKE BYER – PERFORMATIV ARKITEKTUR OG MANGFOLDIG BYKULTUR - Marling, Gitte (K&K - Kultur og Klasse, 2010)
THE CULTURAL INJECTION OF DANISH CITIES – PERFORMATIVE ARCHITECTURE AND DIVERSE URBAN CULTURE This article takes its point of departure in the pressure that the experience economy exerts on cities – a pressure which has been reflected in recent years in a number of comprehensive transformations of physical and architectural environments, leading to the emergence of new “event scapes” related to fun and cultural experience. The physical and cultural consequences of this development are discussed here. However, the article also focuses on the challenges and opportunities that this new “cultural grafting” also generates. It presents a survey that testifies that all Danish municipalities are directly engaged in drawing up strategies for cultural planning. Many interesting small and larger projects have seen the light of day. Three examples of such projects are presented, as they contribute to a new urban cultural agenda that consciously fuses the traditional shopping and café life of the city with knowledge, experience and play. They also contribute to the development of new performative architecture and urban spaces through a new orchestration and performative elements. The article concludes that if we seek strategies for the urban development of our Danish cities that include elements of learning, refinement and culture, factors which are often ignored in the more market-oriented discourses of the experience economy and experience city, then what we need is a broader approach and understanding of the concept of experience. In this case, “experience” will cover many analogous concepts such as discovery, practice and living through something. An approach like this will place new demands on cultural planning and urban design strategies. The examples of cultural projects presented in the article bear witness to an understanding of the experience economy as something with great potential when coupled with strategic thinking and cooperation between public- and private-sector agencies.